2013
DOI: 10.1179/2046905513y.0000000088
|View full text |Cite
|
Sign up to set email alerts
|

Child abuse and neglect in Turkey: professional, governmental and non-governmental achievements in improving the national child protection system

Abstract: Since ratification of the United Nations Convention on the Rights of the Child in 1995, significant efforts were made in Turkey to improve protection of children from abuse and neglect. The government took steps to amend relevant laws. Several state departments recognized the need for professional in-service training of relevant governmental agency staff. University hospitals established numerous hospital-based multidisciplinary child protection centres. The government established an Interministerial Higher Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 17 publications
0
9
0
2
Order By: Relevance
“…It has several impacts on the mental health of children with many short‐term and long‐term negative consequences—anxiety, violent behaviour, trauma, substance abuse, suicide, depression, psychosexual problems, and somatization (Collin‐Vézina, Daigneault, & Hébert, ; Daigneault, Hébert, & Tourigny, ). Although the prevalence of CSA in Turkey is not accurately known, some field studies have reported that 11–37% of selected populations have been sexually abused before the age of 18 (Akco et al, ; Guner, Guner, & Sahan, ). According to the World Health Organization's records, 20% of women and 5–10% of men report that they were exposed to sexual abuse when they were children (World Health Organization, ).…”
Section: Introductionmentioning
confidence: 99%
“…It has several impacts on the mental health of children with many short‐term and long‐term negative consequences—anxiety, violent behaviour, trauma, substance abuse, suicide, depression, psychosexual problems, and somatization (Collin‐Vézina, Daigneault, & Hébert, ; Daigneault, Hébert, & Tourigny, ). Although the prevalence of CSA in Turkey is not accurately known, some field studies have reported that 11–37% of selected populations have been sexually abused before the age of 18 (Akco et al, ; Guner, Guner, & Sahan, ). According to the World Health Organization's records, 20% of women and 5–10% of men report that they were exposed to sexual abuse when they were children (World Health Organization, ).…”
Section: Introductionmentioning
confidence: 99%
“…After the development of this tool, researchers from a wide range of countries converted ICAST to their native languages to report on CAN prevalences, based on a common definition, that can be used in multinational comparisons (Akco et al, 2013;Al Eissa & Almunef, 2010;Annerback, Sahlqvist, Svedin, Wingren, & Gustafsson, 2012;Charak & Koot, 2014;Yanghee & Sangwon, 2011). These studies show that CAN is widespread and causes significant health care problems worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…The UBCPCs are entities established under public universities in Turkey and they consist of an environment to provide education, implementation, and research on diagnosis, treatment, protection, and monitoring of children in need of protection. Similar to the CACs, the UBCPCs are also a non-centralized initiative and they are not refugee-specific ( Akco et al, 2013 ).…”
Section: Steps Taken For Refugee Child Health and Wellbeing By Governmentioning
confidence: 99%